Characterization of the Ubiquitin C-Terminal Hydrolase and Ubiquitin-Specific Protease Families in Rice (Oryza sativa) - Wang, Dong-Hui; Song, Wei; Wei, Shao-Wei; Zheng, Ya-Feng; Chen, Zhi-Shan; Han, Jing-Dan; Zhang, Hong-Tao; Luo, Jing-Chu; Qin, Yong-Mei; Xu, Zhi-Hong; Bai, Shu-Nong (Frontiers in Plant Science, 2018)
The ubiquitin C-terminal hydrolase (UCH) and ubiquitin-specific processing protease (UBP) protein families both function in protein deubiquitination, playing important roles in a wide range of biological processes in animals, fungi, and plants. Little is known about the functions of these proteins in rice (Oryza sativa), and the numbers of genes reported for these families have not been consistent between different rice database resources. To further explore their functions, it is necessary to first clarify the basic molecular and biochemical nature of these two gene families. Using a database similarity search, we clarified the numbers of genes in these two families in the rice genome, examined the enzyme activities of their corresponding proteins, and characterized the expression patterns of all OsUCH and representative OsUBP genes. Five OsUCH and 44 OsUBP genes were identified in the rice genome, with four OsUCH proteins and 10 of 16 tested representative OsUBP proteins showing enzymatic activities. Two OsUCHs and five OsUBPs were found to be preferentially expressed in the early development of rice stamens. Downregulating the stamen-expressed OsUCH genes resulted in a significant reduction in male fertility. This work thus lays down a reliable bioinformatic foundation for future investigations of genes in these two families, particularly for exploring their potential roles in rice stamen development.